Controlling Liquid–Liquid Phase Separation of Cold-Adapted Crystallin Proteins from the Antarctic Toothfish. Issue 24 (7th December 2018) - Bierma, Jan C.; Roskamp, Kyle W.; Ledray, Aaron P.; Kiss, Andor J.; Cheng, C.-H. Christina; Martin, Rachel W.
Abstract: Liquid–liquid phase separation (LLPS) of proteins is important to a variety of biological processes both functional and deleterious, including the formation of membraneless organelles, molecular condensations that sequester or release molecules in response to stimuli, and the early stages of disease-related protein aggregation. In the protein-rich, crowded environment of the eye lens, LLPS manifests as cold cataract. We characterize the LLPS behavior of six structural γ -crystallins from the eye lens of the Antarctic toothfish Dissostichus mawsoni, whose intact lenses resist cold cataract in subzero waters. Phase separation of these proteins is not strongly correlated with thermal stability, aggregation propensity, or cross-species chaperone protection from heat denaturation. Instead, LLPS is driven by protein–protein interactions involving charged residues. The critical temperature of the phase transition can be tuned over a wide temperature range by selective substitution of surface residues, suggesting general principles for controlling this phenomenon, even in compactly folded proteins. Graphical Abstract: Highlights: LLPS plays an important role in many biological functions and disease states. Molecular factors that control LLPS are still not fully understood. Individual proteins of an otherwise cold resistant lens are capable of LLPS. LLPS of tested proteins is not correlated with other commonly observed biophysical properties. Substitution between Arg and Lys can be used to tune the LLPS temperature.